MULTI-LANGUAGE IN THE EDUCATION SYSTEM - Sobor, A.B (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article examines the features of teaching in two languages, using comparative material related to monolingual and bilingual children, mainly in Germany and Azerbaijan. This work presents ideas on the problem of the extra linguistic components of a bilingual personality, which can become the basis for further research in this direction with the involvement of a wide range of scientists (linguists, psychologists, methodologists, etc.) This seems possible, mainly for the reason that the language orientation of the kindergarten also directly influences the behavior of parents in language teaching. By studying linguistic education in kindergarten based on already acquired language skills, we come to the conclusion that these skills are not taken for granted for bilingual or multilingual children. However, it is clear that if children learn to read and write in these languages, they will expand their spoken languages. Natural bilingualism is a plus-sign problem and has its own solutions. But in both cases, natural bilingualism as a problem with a plus sign can be viewed in the same way as a cultural phenomenon and an aspect of intercultural communication. In some cases, a native speaker, when learning a foreign language as a second, learns it through systematically supervised learning and, as a rule, in a different language environment. Specific bilingualism appears when, for many multilingual children, attending a monolingual kindergarten leads to the feeling that outside the family, only the surrounding language is required and important.